2015
DOI: 10.1016/j.jacc.2015.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Referral to Cardiac Rehabilitation of Patients Undergoing Percutaneous Coronary Intervention in the United States

Abstract: Approximately 60% of patients undergoing PCI in the United States are referred for cardiac rehabilitation. Site-specific variation in referral rates is significant and is unexplained by insurance coverage. These findings highlight the potential need for hospital-level interventions to improve cardiac rehabilitation referral rates after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 38 publications
6
116
4
2
Order By: Relevance
“…CR participation rates are alarmingly low, particularly with respect to women and minorities 20. Aragam et al reported a minimal influence of patient demographic factors on rates of CR referral among patients with percutaneous coronary intervention 8. In our study, among eligible cardiovascular patients, we found that females were 15% less likely to receive CR referral than males.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…CR participation rates are alarmingly low, particularly with respect to women and minorities 20. Aragam et al reported a minimal influence of patient demographic factors on rates of CR referral among patients with percutaneous coronary intervention 8. In our study, among eligible cardiovascular patients, we found that females were 15% less likely to receive CR referral than males.…”
Section: Discussioncontrasting
confidence: 42%
“…In our study, we showed that CR referral at hospital discharge was significantly associated with reduced mortality for women and minorities, a group of patients that have traditionally being understudied in the literature. Prior studies suggested that the most significant predictor and easily overcome barrier is the lack of CR referral at hospital discharge 8. We expanded upon prior study by assessing the degree to which the mortality disparity could be reduced by reducing inequality in CR referral at hospital discharge, using a causal mediation analysis approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown et al 32 extracted data from the American Heart Association's Get With The Guidelines program indicated that patients with comorbidity non-ST-segment elevation myocardial infarction, older age would have less chance to receive cardiac rehabilitation services. 32 Aragam et al 35 performed a study enrolling 1432399 patients at 1310 participating hospitals between 2009 and 2012 in the United State, which demonstrated only 60% patients after PCI received cardiac rehabilitation Aragam et al 35 Found that the rate of cardiac rehabilitation referral was associated with hospital characteristics, patient factors and insurance status; and the relevance of three factors gradually declined. All these factors could be overcome.…”
Section: Cardiac Rehabilitation After Pcimentioning
confidence: 99%